NILAI MORAL DALAM FOLKLOR SEBAGAI MEDIA REVOLUSI MENTAL GENERASI MASA DEPAN - Anik Cahyaning Rahayu; Sudarwati . (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
Children and teenagers are the next generation. They need to be prepared physically, mentally,and spiritually. The movement of mental revolution is one of the ways to build the children andteenagers’ characters and develop their mental. This movement aims at changing the society’s mental.Oral literature or folklores may be used as one of the tools to obtain the goal. Folklores are customs andoral tradition told by mouths from one to another generation. Folklores may contain moral teachings andcharacter building that the future generation may learn about. This article discusses the moral valuerepresented in folklores as media for mental revolution. There are 5 folklores, entitled Bawang Merah danBawang Putih, Lutung Kasarung, Keong Mas, Malin Kundang and Cindelaras. The moral teachings ofthose folklores are be patient, sincere, diligent, honest, hard work, faithful, humble, not easilydiscouraged, helpful, full of forgiveness, ungreedy, never looking down others, and respectful towardparents. The previous mentioned moral teachings may contribute to making true the mental change sincemoral values may function to build a good personality.Keywords: folklor, nilai moral, revolusi mental